JUDICIALIZAÇÃO DA SAÚDE E DEMOCRACIA - Lígia Bahia (Universidade do Estado do Rio de Janeiro, 2014)
The "judicialization of health" phenomenon appeared in the area of Collective Health and was immediately construed as a threat to equity, an opposition between individual and collective, wealth and poor, and not as a tension, a conflict between law and rights. In general, the scientific production on the theme is based on assumptions, almost always implicit, on the damages caused to SUS (the Brazilian Public Healthcare Service) by an also assumed noncritical intervention (nontechnical) of the Judiciary. The authors of the studies sought to demonstrate that judicial demands tend to jeopardize a more rational allocation of resources based on epidemiological and clinical criteria and not on the enforceability of the subjective right.